1988
DOI: 10.1259/0007-1285-61-729-806
|View full text |Cite
|
Sign up to set email alerts
|

The renal rind sign: a new ultrasound indication of inflammatory disease in the abdomen

Abstract: The width of the right anterior extrarenal tissue is increased on ultrasound examination in patients with abdominal inflammatory disease. Thickened perirenal fascia associated with acute pancreatitis has previously been reported on computed tomography. A case report has described increased echogenicity of the pararenal space on ultrasound in children with pancreatitis but increased width of the space between the liver and the renal capsule has not hitherto been described in association with inflammatory diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Between the anterior pararenal fascia and the posterior peritoneum there is the anterior pararenal space while between the posterior pararenal fascia and the transversalis fascia there is the posterior pararenal space (6)(7)(8). The fascia cannot be recognized by sonography so the perirenal and pararenal spaces appear as a single compartment filled with fat (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Between the anterior pararenal fascia and the posterior peritoneum there is the anterior pararenal space while between the posterior pararenal fascia and the transversalis fascia there is the posterior pararenal space (6)(7)(8). The fascia cannot be recognized by sonography so the perirenal and pararenal spaces appear as a single compartment filled with fat (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is either a pleural or peritoneal-based rind complicating a mesothelioma in the pleural cavity or a gastrointestinal adenocarcinoma or ovarian cancer in the peritoneal cavity [11]. There have been other appropriations of the term “rind” for sundry ultrasonographic phenomena, but these entities are not pathologically similar to the aforementioned pleural and peritoneal processes [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…With regard to the renal rind, the authors 3,4,6 postulated that changes in the perirenal fascia may be due to localized edema, fibrosis, hyperemia, or lymphatic obstruction. These papers described localized intraabdominal pathologic changes associated with changes in the adjacent perirenal tissues, and their individual authors each believed they were describing a specific sonographic sign of the disease entity presented.…”
Section: A B C Dmentioning
confidence: 99%
“…1,2 The normal perirenal fascia cannot be visualized at sonography, but two studies have measured the "anterior extrarenal space" (the sum of the anterior perirenal plus pararenal spaces) in adults, and the authors have concluded that this space increases in width and echogenicity in association with acute, localized abdominal inflammation, trauma, and malignancy. 3,4 Belli and Joseph 3 coined the term "renal rind sign"as a descriptor for this sonographic finding. In addition, an increase in the width but not the echogenicity of the so-called anterior extrarenal space was noted with chronic, local inflammatory disease and in cushingoid patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation